Egyptian Public’s Knowledge, Attitudes, Perceptions, and Practices toward COVID-19 Infection and Their Determinants. A Cross-Sectional Study, 2020 - Omar, Doaa I.; Amer, Samar A. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The outbreak of coronavirus pandemic in Wuhan, China, since December 2019 has been the major public health concern. With the absence of an effective vaccine or treatment for the disease, current control measures are directed toward preventive measures to lessen disease burden and to curb the spread of the virus. AIM: The aim of the study was to assess knowledge, attitudes, perceptions, and practices (KAPP) of adult Egyptians toward COVID-19 and to study their determinants. METHODS: A community-based cross-sectional survey of a random sample of 999 Egyptian residence aged 16 years and above, it was conducted between April and June 2020 using self-administrated online questionnaire. It consisted of 15, five, and eight questions pertaining to knowledge, attitude, and practices toward COVID-19, respectively, in addition to demographic data. Data were analyzed using SPSS Statistics 23.0 at a level of significant at p ≤ 0.05. RESULTS: Out of the 999 participants, 628 (62.8%) were aged (20-<40y), 666 (66.7%) were females 576 (57.6) from urban residence, 665 (66.7%) were married with university educated or higher 605 (60.5%), and only 105 (10.5%) had chronic diseases. The total knowledge score was significantly higher among highly educated, females, in rural areas, married, and governmental workers, while higher educational status, females, married, smokers, and being without chronic diseases and governmental workers were significantly associated with higher practice scores. CONCLUSIONS: Egyptian participates had good level of knowledge, positive attitude about COVID-19 infection and, poor practice; however, community educational campaigns are necessary to ensure to improve on practice campaigns.